Analisis Implementasi Kampung KB (Keluarga Berkualitas) di Kalurahan Bimomartani, Kapanewon Ngemplak, Kabupaten Sleman - Delta Lucyanita; Mahendra, Gerry Katon (Journal of Social and Policy Issues, 2024)
Bimomartani Quality Family Village is one of the Family Planning Villages in Sleman Regency. The implementation of this policy is based on supporting the government's efforts to ensure good and quality family planning and reducing the number of unplanned births. In its implementation over the past 2 years, there are still problems, namely lack of facilities, budget and low number of family planning users. This research aims to find out how the Kampung KB program is implemented in Bimomartani Village. This research uses qualitative methods by prioritizing primary data from interviews with informants, with the application of George C. Edward III's theory. Data collection techniques use interviews and observation. The research results show (1) transition communication, clarity of information and consistency are implemented effectively. (2) the disposition shows an attitude of commitment and meets the expectations and incentives provided. (3) The bureaucratic structure has clear SOPs and fragmentation. (4) Resources including facilities, human resources and budget are insufficient.